2022
DOI: 10.3390/v14112457
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Otitis Media

Abstract: Otitis media is one of the most common diseases in children, with 80% of children experiencing it by the age of three years. Therefore, the resulting social burden is enormous. In addition, many countries still suffer from complications due to otitis media. Meanwhile, COVID-19 has affected many diseases, with otitis media being one of the most strongly affected. This review aims to find out how COVID-19 has affected otitis media and its significance. A series of measures brought about by COVID-19, including em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Our findings regarding the observed differences in both trends in episodes [ 47 51 ] and low-value services are in line with previous studies in hospital care [ 27 , 52 54 ]. Hence, both the number and rates of episodes and low-value care provision were largely affected during the first months of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings regarding the observed differences in both trends in episodes [ 47 51 ] and low-value services are in line with previous studies in hospital care [ 27 , 52 54 ]. Hence, both the number and rates of episodes and low-value care provision were largely affected during the first months of the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…This study has implications for future research. Some studies have shown that the measures taken in response to coronavirus disease of 2019, including an emphasis on personal hygiene and social distancing, may have had a positive impact on the occurrence of otitis media ( Choi et al 2022 ). However, necessary vaccinations may be delayed because of social distancing, which may increase the risk of vaccine-preventable otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…Such challenges can lead to delays in proper treatment, and potentially result in errors or overmedication. Moreover, the COVID-19 patients were found to have relationship with Otitis media ( Choi et al, 2022 ), they demand to be diagnosed earlier than before, as otitis media always intend to recurrence and even cause Sensorineural-hearing-loss ( Xia et al, 2022 ). As a result, achieving rapid differential diagnosis for otitis media is crucial to ensure optimal patient outcomes, in this situation, an efficient diagnosis can be given using our transfer learning model.…”
Section: Discussionmentioning
confidence: 99%